Effect of bioactive glass air-abrasion on Fusobacterium nucleatum and Porphyromonas gingivalis biofilm formed on moderately rough titanium surface - Abushahba Faleh; Gürsoy Mervi; Hupa Leena; Närhi Timo O (United States, 2022)
This aim of this study was to investigate the effects of three types of air-abrasion particles on dual-species biofilms of Fusobacterium nucleatum and Porphyromonas gingivalis, both of which were cultured on sandblasted and acid-etched (SA) titanium discs. Out of 24 SA discs with biofilm, 18 were exposed to either air-abrasion using Bioglass 45S5 (45S5 BG; n = 6), novel zinc (Zn)-containing bioactive glass (Zn4 BG; n = 6), or inert glass (n = 6). The efficiency of biofilm removal was evaluated using scanning electron microscopy (SEM) imaging and culturing techniques. Air-abrasion using 45S5 BG or Zn4 BG demonstrated a significant decrease in the total number of viable bacteria compared to discs air-abraded with inert glass or intact biofilm without abrasion. Moreover, P. gingivalis could not be detected from SEM images nor culture plates after air-abrasion with 45S5 BG or Zn4 BG. The present study showed that air-abrasion with 45S5 or Zn4 bioactive glasses can successfully eradicate dual-biofilm of F. nucleatum and P. gingivalis from sandblasted and acid-etched titanium discs.